Augmented Reality With Cinematic Rendered 3-Dimensional Images From Volumetric Computed Tomography Data. Issue 1 (22nd September 2022) - Rowe, Steven P.; Schneider, Robert; Krueger, Sebastian; Pryde, Valerie; Chu, Linda C.; Fishman, Elliot K.
Abstract: Recent advances in 3-dimensional visualization of volumetric computed tomography data have led to the novel technique of cinematic rendering (CR), which provides photorealistic images with enhanced surface detail and realistic shadowing effects that are generally not possible with older methods such as volume rendering. The emergence of CR coincides with the increasingly widespread availability of virtual reality (VR)/augmented reality (AR) interfaces including wearable headsets. The intersection of these technologies suggests many potential advances, including the ability of interpreting radiologists to look at photorealistic images of patient pathology in real time with surgeons and other referring providers, so long as VR/AR headsets are deployed and readily available. In this article, we will present our initial experience with viewing and manipulating CR images in the context of a VR/AR headset. We include a description of key aspects of the software and user interface, and provide relevant pictorial examples that may help potential adopters understand the initial steps of using this exciting convergence of technologies. Ultimately, trials evaluating the added value of the combination of CR with VR/AR will be necessary to understand the potential impact of these methods on medical practice.